2008
DOI: 10.1016/j.bmc.2008.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antifungal properties of N-thiolated β-lactams

Abstract: N-thiolated beta-lactams had previously been shown to have antibacterial activity against a narrow selection of pathogenic bacteria including Staphylococcus aureus and Bacillus anthracis, as well as apoptotic-inducing activity in a variety of human cancer cell lines. We now have found that these lactams also possess antifungal activity against Candida and other fungi by exerting powerful cytostatic effects that disrupt the structural integrity of cytoplasmic membranes. The mode of action and structure-activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Compounds 70 and 71 actually resulted active even if they appeared to be more active against S. aureus than MRSA, which is opposite to what previously observed for the Nthiolated -lactams. Turos also reported that some N-thiomethyl--lactams showed apoptotic-inducing activity [75] on some human cancer cell lines as well as antifungal activity on Candida fungi [76]. Selected compounds exhibited moderate apoptosis-inducing properties in a variety of human cancer cell inducing DNA damage that leads to apoptosis preferentially in cancer and transformed over normal/non transformed cells.…”
Section: N-thiolated-azetidinonesmentioning
confidence: 96%
“…Compounds 70 and 71 actually resulted active even if they appeared to be more active against S. aureus than MRSA, which is opposite to what previously observed for the Nthiolated -lactams. Turos also reported that some N-thiomethyl--lactams showed apoptotic-inducing activity [75] on some human cancer cell lines as well as antifungal activity on Candida fungi [76]. Selected compounds exhibited moderate apoptosis-inducing properties in a variety of human cancer cell inducing DNA damage that leads to apoptosis preferentially in cancer and transformed over normal/non transformed cells.…”
Section: N-thiolated-azetidinonesmentioning
confidence: 96%
“…With the microbes responding to the traditional antibiotics through β-lactamases, the need for novel antibiotics prevails, making synthesis of newer β-lactams ever more important. In addition to their use as antibiotics, β-lactams are increasingly being used as synthons for other biologically important molecules [2][3][4][5][6][7][8][9][10][11]. β-Lactams have been found to act as cholesterol acyl transferase inhibitors [12], thrombin inhibitors [13], human cytomegalovirus protease inhibitors [14], matrix metalloprotease inhibitors [15], cysteine protease [16], and apoptosis inductors [17].…”
Section: Introductionmentioning
confidence: 99%
“…With this view, the present study was designed to evaluate the antimicrobial activity of some new 2'-phenyl-4'-[3"-(2"-oxo-1"H-indolidene)-5'-oxo-imdazolyl]-1'-[{p-1(4-aryl-1-biphenyl}] / 4-aryl-3-chloro azetidinones (6a-e and 7a-d) consisting of three well established pharmacologically active nucleiimidazole, azole, and β-lactam [15][16][17][18][19] ring in one molecular union (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%